Long‐term effectiveness of ustekinumab comparable to antitumor necrosis factor agents in patients with Crohn's disease. Issue 11 (16th September 2022) - Shiga, Hisashi; Tarasawa, Kunio; Moroi, Rintaro; Makuuchi, Motoki; Takahashi, Takahiro; Shimoyama, Yusuke; Kuroha, Masatake; Kakuta, Yoichi; Fushimi, Kiyohide; Fujimori, Kenji; Kinouchi, Yoshitaka; Masamune, Atsushi
Abstract: Background: Ustekinumab (UST), an antibody against the p40 subunit of interleukin‐12/23, has been proven to be effective in patients with Crohn's disease (CD). However, large, long‐term comparative studies of UST against anti‐‐tumor necrosis factor (TNF) agents are lacking. We compared the effectiveness of anti‐TNF agents and UST in CD patients without prior use of biologics. Methods: We used a large nationwide anonymized Japanese database containing administrative medical claims data and various related patient data. In a propensity score‐matched cohort with similar clinical characteristics, 2‐year effectiveness was compared between patients treated with infliximab or adalimumab (anti‐TNF group) and those treated with UST (UST group). Primary outcomes were cumulative rates of hospitalization, surgery, and persistence. Results: Among 53 540 CD patients, 7047 were extracted for eligibility, of which 5665 were treated with an anti‐TNF agent and 1382 with UST. After propensity score matching, the cumulative hospitalization rates were comparable between anti‐TNF and UST groups ( P = 0.85; 25.3% vs 26.5% at 1 year, 33.8% vs 39.8% at 2 years). The cumulative surgery rates were also comparable between these groups ( P = 0.46; 5.5% vs 5.1% at 1 year, 8.3% vs 8.4% at 2 years). The persistence rate at 1 year was higher in UST group (90.8% vs 92.5%), and that at 2 years was higher in anti‐TNF group (81.2% and 74.6%); however, there was no significant difference in the cumulative persistence rate ( P = 0.55). Conclusions: Anti‐TNF agents and UST appear to have comparable effectiveness for CD patients without prior use of biologics.